Detection of early relapse in multiple myeloma patients - Růžičková, Tereza; Vlachová, Monika; Pečinka, Lukáš; Brychtová, Monika; Večeřa, Marek; Radová, Lenka; Ševčíková, Simona; Jarošová, Marie; Havel, Josef; Pour, Luděk; Ševčíková, Sabina (Cell division, 2025)
BACKGROUND: Multiple myeloma (MM) represents the second most common hematological malignancy characterized by the infiltration of the bone marrow by plasma cells that produce monoclonal immunoglobulin. While the quality and length of life of MM patients have significantly increased, MM remains a hard-to-treat disease; almost all patients relapse. As MM is highly heterogenous, patients relapse at different times. It is currently not possible to predict when relapse will occur; numerous studies investigating the dysregulation of non-coding RNA molecules in cancer suggest that microRNAs could be good markers of relapse. RESULTS: Using small RNA sequencing, we profiled microRNA expression in peripheral blood in three groups of MM patients who relapsed at different intervals. In total, 24 microRNAs were significantly dysregulated among analyzed subgroups. Independent validation by RT-qPCR confirmed changed levels of miR-598-3p in MM patients with different times to relapse. At the same time, differences in the mass spectra between groups were identified using matrix-assisted laser desorption/ionization time of flight mass spectrometry. All results were analyzed by machine learning. CONCLUSION: Mass spectrometry coupled with machine learning shows potential as a reliable, rapid, and cost-effective preliminary screening technique to supplement current diagnostics.
Keywords: Multiple myeloma; microRNA; Machine learning; MALDI-TOF MS; Liquid biopsy; Relapse; Small RNA seq